Large scale quantum walks by means of optical fiber cavities. (23rd August 2016) - Boutari, J; Feizpour, A; Barz, S; Franco, C Di; Kim, M S; Kolthammer, W S; Walmsley, I A
Abstract: We demonstrate a platform for implementing quantum walks that overcomes many of the barriers associated with photonic implementations. We use coupled fiber-optic cavities to implement time-bin encoded walks in an integrated system. We show that this platform can achieve very low losses combined with high-fidelity operations, enabling an unprecedented large number of steps in a passive system, as required for scenarios with multiple walkers. Furthermore the platform is reconfigurable, enabling variation of the coin, and readily extends to multidimensional lattices. We demonstrate variation of the coin bias experimentally for three different values.